Benign cementoblastoma: A rare case report with review of literature - Neeta Sharma (Wolters Kluwer Medknow Publications, 2014)
We present a rare case of radiopaque lesion with radiolucent rim in the right body of mandible, with history of extraction of involved tooth, which made diagnosis confusing unless pre-extraction intraoral periapical radiography radiograph was recovered, finally diagnosed as benign cementoblastoma. It was surgically managed, with no recurrence of the lesion more than 2 years of follow-up. Benign cementoblastoma is a rare, benign tumor of odontogenic ectomesenchymal origin, usually associated with roots of first mandibular molar.